Long chain branched impact copolymer of polypropylene: microstructure and rheology - Chikhalikar, Kalyani; Deshpande, Anushree; Pol, Harshawardhan; Dhoble, Deepa Arun; Jha, Saroj; Jadhav, Kishor; Mahajan, Sunil; Ahmad, Zubair; Kulkarni, Surendra; Gupta, Surendra; Lele, Ashish K. (Polymer Engineering and Science, 2015)
A biphasic impact copolymer of polypropylene (ICP) was modified with peroxide by reactive extrusion process resulting in reduced melt flow index, improved melt strength, and higher die swell. The polymers were for the first time subjected to systematic rheological and microstructural characterization in an effort to understand their structure-property relations. In shear rheological tests, the modified ICP displayed higher flow activation energy, reduced values of loss tangent and nearly equal frequency dependence of storage and loss modulli. The modified ICP also showed strain hardening behaviour in uniaxial extensional rheology and higher crystallization temperature in differential scanning calorimetry (DSC). All these are definitive indications of the presence of long chain branches (LCB). Fitting the rheological data of modified ICPs with the eXtended Pom Pom (XPP) model indicated the presence of LCB on the higher molecular weight fraction in the polymer, a result which was corroborated with multi-detector high temperature gel permeation chromatography (HT-GPC). More importantly, the matrix and rubber phases of the ICP were separately characterized for presence of long chain branching by rheology, DSC and HT-GPC. The results indicate that while LCB existed in the matrix phase, microgels were present in both phases indicating that the reaction with peroxide occurred in both phases. POLYM. ENG. SCI., 55:1463-1474, 2015. (c) 2014 Society of Plastics Engineers

Luminescent 3D printed poly(lactic acid) nanocomposites with enhanced mechanical properties - Kothavade, Premkumar Anil; Yadav, Prashant; Nidhankar, Aakash D.; Torris, Arun; Pol, Harshawardhan; Kafi, Abdullah; Bateman, Stuart; Sukumaran, Santosh Babu; Shanmuganathan, Kadhiravan (Polymer Engineering and Science, 2023)
The three-dimensional (3D) printing of functional composite materials has gained tremendous interest in recent years. Nevertheless, research on 3D printing of luminescent composite materials is very limited, and the mechanical properties of such 3D-printed composites are poor. Herein, we report the preparation and characterization of a poly(lactic acid) (PLA) composite that, when 3D printed, exhibits enhanced toughness and high solid-state fluorescence quantum yield. Incorporation of only 1 wt% pyrene butyric acid modified cellulose nanofibers (PBA-m-CNF) and l0 wt% thermoplastic polyurethane (TPU) into PLA led to 223% increase in toughness and 21% increase in tensile modulus of PLA. Scanning electron microscopy (SEM) and X-ray microcomputed tomography (mu-CT) analysis of the fractured cross-sections of 3D printed composites revealed a ductile failure mode. The PLA/PBA-m-CNF1/TPU10 3D printed composite also exhibited a high solid-state fluorescence quantum yield of 38.35%. To the best of our knowledge, this is the first report to show both enhanced mechanical properties and high solid-state fluorescence emission for 3D printable PLA. Such functional PLA composites could have potential applications in the fabrication of complex-shaped sensors, optical light pipes, etc.
Keywords: 3D printing; Composite; fluorescence; Nanocellulose; poly(lactic acid); toughness